40-Year-Old Female Presents with Intestinal Malrotation and Hemorrhagic Ovarian Cyst: A case report and review of the literature - Sabrina Berdouk; Obaida Farouk (Saudi Journal of Emergency Medicine)
Background: Intestinal malrotation is a congenital anomaly that refers to the failure of the normal fetal rotation of intestines around the superior mesenteric artery and their fixation in the peritoneal cavity, which happens between weeks 5-12 of embryological development. Most of the cases are discovered during the first year of life where the baby presents with abdominal cramps and bilious vomiting due to small bowel obstruction or volvulus. Globally, adult cases are rare and make about 0.2% of all cases discovered all over the world, while there is no data published in UAE on adult cases till date. 15% of adults with confirmed intestinal malrotation can stay asymptomatic throughout life, while the rest may present either chronically with frequent abdominal pains together with irregular bowl habits, or acutely with bowel obstruction, intestinal ischemia or volvulus. These symptoms are caused by Ladd's bands: peritoneal bands that run from the cecum to the right lateral abdominal wall. Rotational anomalies of intestines require surgical treatment ( Ladd's procedure) if they are symptomatic. Though they are often difficult to diagnose, rapid recognition and surgical treatment usually lead to successful outcome. In the following report, we present a case of a patient who presented with acute on chronic abdominal pain, with clinical findings of right adnexal hemorrhagic cyst along with intestinal malrotation is discussed. Summary: Our patient was a 40-year-old female who has been experiencing chronic abdominal pian throughout her life. The pain was always related by her physicians to adenomyosis and IBS. She underwent multiple ultrasound studies of the abdomen, multiple MRI studies of the pelvis ,2 LSCS with bilateral tubectomy and a laparoscopic cholecystectomy previously without being diagnosed with intestinal malrotation. The patient presented with right lower abdominal pain together with fever for 5 days, in addition she vomited once. The pain was not similar the pain she was used to have as her chronic pain was always colicky and more to the lower and left side of the abdomen. On physical examination, she had a positive McBurney's point and right iliac fossa tenderness with guarding. CT of the abdomen and pelvis was consistent with right adnexal mass that was approved later to be hemorrhagic cyst by an MRI. The CT showed a picture of complete intestinal malrotation where there was reversal of SMA/SMV axis. Duodenojejunal flexure was located on the right side of the spine. The Small bowels were entirely located on the right side with the large bowels located entirely on the left side. The cecum was in the midline on the right of rectosigmoid. A laparoscopic excision of the cyst was performed, and the patient was educated on her condition and advised to return if any symptoms arise. The cause and incidence of intestinal malrotation in adults is discussed in this report as the first case of intestinal malrotation in adults to be published in the UAE. Conclusion: Intestinal malrotation is adults is rare and can present as either acute intestinal obstruction or chronic abdominal pain. The best surgical management is performing the Ladd's procedure to prevent intestinal ischemia and volvulus. [SJEMed 2024; 5(1.100): S38-S38]